Śāstradīpikāyastarkapādaḥ: Paṇḍitaśrīmaṇidrāviḍaśāstrikṛtavivṛtisahitaḥ - Pārthasārathi Miśra (Ambika Aksharavali, 2015)
Commentary with supercommentary on Jaimini's Mīṃāmsāsūtra, basic work on Mīmansā philosophy